Effect of Soy Milk Consumption on Quality of Life in Iranian Postmenopausal Women. - Mansoreh Norrozi; Fedyeh Haghollahi; Fatemeh Ramezanzadeh; Parichehr Hanachi (Tehran University of Medical Sciences, 2015)
To find out whether or not soy milk as a phytoestrogen product can improve the quality of life of the Iranian postmenopausal women.Participants of this randomized clinical trial were 57 healthy postmenopausal women. All eligible women were randomly divided into two groups of soy milk (SG) and control (CG). Individuals in the SG (n = 34) received 500 ml soy milk including genistein (28.86 mg/dl) and daidzein (8.25 mg/dl) per day, while the participants in the CG (n = 23) received 500 ml low fat cow milk per day during 8 months. Both groups also took daily calcium-D capsules (500 mg calcium and 200 IU D3). The quality of life of all participants was examined twice (at the baseline and the end of the eighth month) using the menopause-specific quality of life (MENQOL) questionnaire.A total of 57 healthy postmenopausal women with a mean age of 52.13 (3.05) years were included in this study. Despite the significant but weak difference was observed between SG and CG in the sexual domain score (the mean of percent change: 0.46% vs. 33.94%, respectively; p = 0.031), while significant relationship was found between the soy milk consumption and improvement in the domains studied (vasomotor, psychosocial and physical).Overall our findings showed that soy milk does not improve the quality of life in postmenopausal women. But to achieve more reliable results, it is recommended further study to be done with a larger sample size, more prolonged, and with participants having severer vasomotor symptoms.